A Borehole Test for Chlorinated Solvent Diffusion and Degradation Rates in Sedimentary Rock. Issue 2 (29th January 2022) - Allen‐King, Richelle M.; Kiekhaefer, Rebecca L.; Goode, Daniel J.; Hsieh, Paul A.; Lorah, Michelle M.; Imbrigiotta, Thomas E.
Abstract: We present a new field measurement and numerical interpretation method (combined termed "test") to parameterize the diffusion of trichloroethene (TCE) and its biodegradation products (DPs) from the matrix of sedimentary rock. The method uses a dual‐packer system to interrogate a low‐permeability section of the rock matrix adjacent to a previously contaminated borehole and uses the borehole monitoring history to establish the pretest condition. TCE and its DPs are removed from the groundwater between the packers at the onset of the testing. The parameters estimated by fitting a radial diffusion model to the concentration history and borehole concentration data, also termed back diffusion, are the tortuosity factor and sorption coefficients of TCE and DPs in the rock matrix and the TCE and DP biodegradation rate coefficients in the borehole. We demonstrate the equipment design and the interpretive method using a borehole accessing the gray mudstone at a TCE contaminated site in the Newark Basin. In this test, both nonreactive (bromide) and reactive (trichlorofluoroethene) tracers are used to constrain the estimated parameters; however, the bromide tracer was not needed to estimate the parameters in this test. The parameters estimated from the field test are consistent with values measured independently in laboratory experiments using field samples of similar lithology. From the interpretation, we compute the TCE and DP concentration distributions in the rock matrix prior to the test to illustrate how the results can be used to enhance understanding of contaminant distribution in the rock matrix. Abstract : Article Impact Statement : Field test determines trichloroethene effective diffusion and sorption coefficients in rock matrix and biodegradation rate in borehole.